Blended Learning Model in the Indonesian Language Learning during the Covid-19 Period - Cecep Wahyu Hoerudin (AL-ISHLAH: Jurnal Pendidikan, 2022)
Throughout the COVID-19 epidemic, learning activities were conducted online. Students’ capacity to comprehend the content offered by the teacher is significantly impacted when they learn through this online technique. This also occurs in the subject of Indonesian. As a result, innovation is required to enhance students’ comprehension and abilities when learning Indonesian, namely through blended learning. This study aims to collect data on the blended learning model’s implementation in Indonesian language subject during the Covid-19 pandemic. This descriptive qualitative research method entails locating data sources through literature searches for subsequent analysis. The results indicated that the blended learning model is an excellent model for Indonesian language learning during the epidemic and the new normal. It allows students and teachers to learn autonomously, be helpful, and improve. The blended learning model’s purpose is to assist students in developing their learning styles and preferences for learning; to provide practical, realistic opportunities for educators and students to learn independently, be helpful, and continue to grow; to increase scheduling flexibility for learners by combining the best features of face-to-face and online instruction; to engage students in interactivity during face-to-face classes. At the same time, the online component gives students rich multimedia content at any time and from any location as long as they have access to the objective.